WS Rendra dan teater mini kata - Yudiaryani, 1956- (Baciro, Yogyakarta : Galang Pustaka : Institut Seni Indonesia Yogyakarta, 2015)
Criticism and interpretation on works of W.S. Rendra, a famous Indonesian poet and dramatist.
Revision of the author's thesis (doctoral)--Universitas Gadjah Mada, Yogyakarta.
Includes bibliographical references.
In Indonesian.
Koleksi Sumbangan : Zainal Abidin Abdul Wahid.
Keywords: Rendra, W. S. -- 1935- -- Criticism and interpretation; Indonesian poetry -- History and criticism